Advances in InP/Ga(In)AsSb double heterojunction bipolar transistors (DHBTs). (20th March 2019) - Bolognesi, Colombo R; Quan, Wei; Arabhavi, Akshay M; Saranovac, Tamara; Flückiger, Ralf; Ostinelli, Olivier; Wen, Xin; Luisier, Mathieu
Abstract: Double heterojunction bipolar transistors (DHBTs) are intended to extend the breakdown voltage beyond what is possible in single heterojunction bipolar transistors, ideally without sacrificing frequency performance. InP/GaAsSb DHBTs offer the most favorable cutoff frequency versus breakdown voltage tradeoff among all bipolar transistors. It has been shown that the addition of Indium to a GaAsSb base further increases current gain cutoff frequencies f T . In the present article, we compare ternary (GaAsSb) and quaternary (GaInAsSb) graded base DHBTs fabricated side-by-side to shed light on the physical mechanism responsible for the increase in cutoff frequencies. Ternary and quaternary base DHBTs show markedly distinct RF behaviors when measured at reduced temperatures—we use these differences to infer that the improved cutoff frequencies with GaInAsSb base layers arise because of a reduced electron population of the L-valley with increasing In-content in the base. A quantum transport calculation based on the non-equilibrium Green's function formalism and the empirical tight-binding method for electron transport through the base and collector regions with different Γ-L separations for different temperatures reproduces the main experimentally observed features.